Degradation of tetracycline antibiotic utilizing light driven-activated oxone in the presence of g-C3N4/ZnFe LDH binary heterojunction nanocomposite - Soltani, Reza Darvishi Cheshmeh; Abolhasani, Elham; Mashayekhi, Masoumeh; Jorfi, Najla; Boczkaj, Grzegorz; Khataee, Alireza (Pergamon-Elsevier Science Ltd, 2022)
In the present study, a binary heterojunction nanocomposite composed of graphitic carbon nitride (g-C3N4) and Zn/Fe-contained layered double hydroxide (ZnFe LDH) was employed as heterogeneous catalyst for the decomposition of tetracycline (TC) antibiotic utilizing Oxone and UV light irradiation. The sole use of g-C3N4/ ZnFe LDH as adsorbent led to the negligible elimination of TC. In addition, the sole use of Oxone or UV (photolysis) and even their combination were not effective enough to degrade the target pollutant, while the combined process of g-C3N4/ZnFe LDH/Oxone/photolysis revealed significantly enhanced (synergistic) degradation of TC (92.4% within 30 min). Indirect detection tests for the identification of free radical species indicated the major role of both hydroxyl (.OH) and sulfate (SO4.-) radicals in the degradation of TC by the g-C3N4/ZnFe LDH/Oxone/photolysis system. The elimination of TC followed a pseudo-first order kinetic model. The complete degradation of TC (degradation efficiency of 100%) was achieved within the reaction time of 25 min when ultrasound (US) was applied as enhancing agent. Furthermore, the results of total organic carbon (TOC) analysis were used to exhibit progress in the mineralization of the pollutant. The bioassay results indicated the decreased toxicity of the process effluent toward microbial population of Escherichia coli after the treatment.
Keywords: Tetracycline; Peroxymonosulfate; Graphitic carbon nitride; Layered double hydroxides; Heterojunction catalyst; Advanced oxidation processes (AOPs)